2023
DOI: 10.22159/ijap.2023v15i1.46369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Stk630921 Interactions to Interleukin-17a

Abstract: Objective: This research aimed to investigate the stability of the STK630921-Interleukin 17A (IL-17A) complex and to predict important residues that interact during molecular dynamics simulations. Methods: Molecular docking simulations were performed, followed by molecular dynamics (MD) simulations and the free energy of binding calculations using YASARA-Structure. The identification of interacting residues was done using PyPLIF HIPPOS. Molecular docking simulations were performed on the IL-17A binding pocket … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several prior studies have leveraged the PyPLIF-HIPPOS combination alongside MD simulations for various purposes. This combination effectively elucidated the stability of the interleukin-17A complex with the small molecule STK630921 (Riandono & Istyastono, 2023). Subsequent research demonstrated the capability of this combination to discern interaction hotspots between dipeptidyl peptidase IV (DPP4) and its inhibitor, caffeic acid, through the course of MD simulations (Istyastono & Riswanto, 2022).…”
Section: Resultsmentioning
confidence: 97%
“…Several prior studies have leveraged the PyPLIF-HIPPOS combination alongside MD simulations for various purposes. This combination effectively elucidated the stability of the interleukin-17A complex with the small molecule STK630921 (Riandono & Istyastono, 2023). Subsequent research demonstrated the capability of this combination to discern interaction hotspots between dipeptidyl peptidase IV (DPP4) and its inhibitor, caffeic acid, through the course of MD simulations (Istyastono & Riswanto, 2022).…”
Section: Resultsmentioning
confidence: 97%